2014
DOI: 10.1063/1.4868514
|View full text |Cite
|
Sign up to set email alerts
|

Performance of large electron energy filter in large volume plasma device

Abstract: This paper describes an in-house designed large Electron Energy Filter (EEF) utilized in the Large Volume Plasma Device (LVPD) [S. K. Mattoo, V. P. Anita, L. M. Awasthi, and G. Ravi, Rev. Sci. Instrum. 72, 3864 (2001)] to secure objectives of (a) removing the presence of remnant primary ionizing energetic electrons and the non-thermal electrons, (b) introducing a radial gradient in plasma electron temperature without greatly affecting the radial profile of plasma density, and (c) providing a control on the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The sandwiched EEF plasma region proposes a complex plasma scenario. We observed that energetic electrons are trapped in the mirror of the solenoid field of the EEF in the source plasma region of LVPD and no trace of these electrons is observed in the target region [36]. The transport across EEF magnetic field helps in producing a plasma profile suitable for the excitation of ETG instability, in axially far-off region, approximately away from the EEF surface.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…The sandwiched EEF plasma region proposes a complex plasma scenario. We observed that energetic electrons are trapped in the mirror of the solenoid field of the EEF in the source plasma region of LVPD and no trace of these electrons is observed in the target region [36]. The transport across EEF magnetic field helps in producing a plasma profile suitable for the excitation of ETG instability, in axially far-off region, approximately away from the EEF surface.…”
Section: Methodsmentioning
confidence: 86%
“…Also, establishing an independent control over density and temperature profiles is proved to be a difficult task. We dressed LVPD plasma to meet these requirements by inventing a large-sized electron energy filter [1,36] . The filter is a solenoid having rectangular cross section with 82% transparency and is placed across the diameter of the LVPD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnet coils are powered with a power supply of capacity 600 A/300 V. A rectangular solenoid with varying aspect ratio but with a constant axial width of 0.04 m, called as electron energy filter (EEF), is installed at the axial center of the device. The EEF [19] produces a strong transverse (B EEF (x) ⊥B z ) magnetic field, B EEF ∼ 0.016 T with respect to the axial magnetic field, B z ∼ −6.2 × 10 −4 T. The EEF redefines the plasma volume in LVPD as source, EEF and target plasma regions. The present investigations are limited to the source plasma region, as marked in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…x respectively. The pulsed Argon plasma (∆ = t 9.2 ms) is produced at a fill pressure of = × − P 4 10 mbar 4 by using a tungsten based multi-filamentary cathode [23].…”
Section: Methodsmentioning
confidence: 99%